2011
DOI: 10.1002/jsfa.4586
|View full text |Cite
|
Sign up to set email alerts
|

Facilitative effects of Eucommia ulmoides on fatty acid oxidation in hypertriglyceridaemic rats

Abstract: This study indicates that the promotion of fatty acid oxidation, probably by the action of phytochemicals, participates in the ameliorative effect of E. ulmoides leaves on hypertriglyceridaemia. These findings provide the scientific evidence for the functionality of E. ulmoides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Likewise, 0.1% lipoic acid increased beta-oxidation and decreased cholesterol synthesis and oxidative stress by increasing those of free radical scavenger enzyme gene expression in liver of C57BL/6 mice [103]. In rats fed a high-fat/high-fructose diet, compounds present in Eucommia ulmoides tea (4 or 20 g/L extract) also increased expression of genes involved in hepatic alpha-, beta-, and omega-oxidation, mainly related to the peroxisome proliferator-activated receptor alpha and delta signaling pathways [104]. Furthermore, combined quercetin and resveratrol supplementation resulted in significant restoration of gene sets in pathways of glucose/lipid metabolism, liver function, cardiovascular system, and inflammation/immunity, which were altered by high fat diet feeding [105].…”
Section: Effect Of Dietary Fat Contentmentioning
confidence: 99%
“…Likewise, 0.1% lipoic acid increased beta-oxidation and decreased cholesterol synthesis and oxidative stress by increasing those of free radical scavenger enzyme gene expression in liver of C57BL/6 mice [103]. In rats fed a high-fat/high-fructose diet, compounds present in Eucommia ulmoides tea (4 or 20 g/L extract) also increased expression of genes involved in hepatic alpha-, beta-, and omega-oxidation, mainly related to the peroxisome proliferator-activated receptor alpha and delta signaling pathways [104]. Furthermore, combined quercetin and resveratrol supplementation resulted in significant restoration of gene sets in pathways of glucose/lipid metabolism, liver function, cardiovascular system, and inflammation/immunity, which were altered by high fat diet feeding [105].…”
Section: Effect Of Dietary Fat Contentmentioning
confidence: 99%
“…The bark of E. ulmoides (Cortex Eucommia) has been traditionally used as an herbal medicine with analeptic, analgesic, sedative, antihypertensive, and diuretic effects in Japan, China, and Korea. In vitro and in vivo studies indicated that the compounds and extracts from Eucommia ulmoides have various pharmacological effects in treating hypertension [10][11][12][13], hyperlipidemia [14,15], diabetes [16], obesity [14,[17][18][19][20], osteoporosis [21][22][23][24][25][26], and lupus-like syndrome [27], and promoting neuroprotection [28,29] and immunoregulation [30]. E. ulmoides leaves and barks have the same iridoid and lignin compound components; therefore, the leaves have been used similarly as the bark, as tonic and antihypertensive.…”
Section: Introductionmentioning
confidence: 99%
“…Among the effects of ELE, many anti-obesity effects have been studied from the viewpoint of preventing lifestyle diseases. Therefore, we proposed that ELE ingestion might prevent the obesity caused by nocturnal eating, as ELE ingestion reduces food intake and water consumption during the light phase (i.e., inactive period) in rats [7,14,15]. On the other hand, it has been reported that appetite suppression due to the inhibition of the parasympathetic nervous system, which controls the gastrointestinal tract, is related to the suppression of feeding and the improvement…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the study of Eucommia leaf extract (ELE) has been focused on its efficacy in maintaining human health. Reports on the biogenic effectiveness of ELE ingestion have identified the following benefits: 1) antihyperlipidemic effects that reduce visceral fat and suppress elevated levels of triglyceride and cholesterol in the blood [1][2][3][4][5][6][7]; 2) effects on bone, such as preventing the onset of postmenopausal osteoporosis and promoting calcium accumulation in osteoblasts [8][9][10]; 3) antihypertensive effects that slowly decrease blood pressure by maintaining the flexibility of the blood vessels and promoting arterial smooth muscle relaxation [2,11]; 4) rapid eye movement sleep and non-rapid eye movement sleep inducing effect [12]; and 5) preventative effects on ulcerative colitis by asperuloside, one of the major components of ELE [13]. Thus, ELE promotes systemic health.…”
mentioning
confidence: 99%